(untitled) (KULT_online, 2012)
With his monograph Doing Generation (2011) Björn Bohnenkamp succeeds in putting generation studies on the map of the study of culture. As the title indicates, he claims that generations are nothing natural but are always the product of formation processes. The study combines current theoretical discussions about the emergence, continuity, and relevance of generations with an analysis of German pop novels, magazines, and internet forums that make significant contributions to the academic discussion about generations and their popularity. The analysis is further complemented by theories and approaches from the field of the study of culture, as the reference to works by Judith Butler in the title shows. That the selection of the three written media has not yet been systematically analysed for their potential to trigger the formation of generations seems to be due to the traditional prevalence of the fields of history, political and social sciences in this field of research. It is the main achievement of Doing Generation to close this research gap.